Immune Evasion and Drug Resistance Mediated by USP22 in Cancer: Novel Targets and Mechanisms - Guo, Jinhui; Zhao, Jie; Fu, Wen; Xu, Qiuran; Huang, Dongsheng (Frontiers in Immunology, 2022)
Regulation of ubiquitination is involved in various processes in cancer occurrence and development, including cell cycle arrest, cell proliferation, apoptosis, invasion, metastasis and immunity. Ubiquitination plays an important role not only at the transcriptional and post-translational levels, but also at the protein level. When ubiquitination is in a pathological state, abnormally activated biological processes will not only induce cancer progression, but also induce immune evasion. The main function of deubiquitinases (DUBs) is to remove ubiquitin chains from substrates, changing the biological activity of the substrates. It has great potential to improve the prognosis of cancer by targeting deubiquitinase to regulate proteome. Ubiquitin specific peptidase 22 (USP22) belongs to the ubiquitin-specific proteases (USPs) family of DUBs and has been reported to be related to various physiological and pathological processes. USP22 is abnormally expressed in various malignant tumors such as prostate cancer, lung cancer, liver cancer and colorectal cancer, which suggests that USP22 may play an important role in tumors. USP22 may stabilize programmed death ligand 1 (PD-L1) by deubiquitination, while also regulating T cell infiltration into tumors. In this article, we review and summarize the biological functions of USP22 in multiple signal transduction pathways during tumorigenesis, immune evasion, and drug resistance. Furthermore, we propose a new possibility of combining USP22 with chemotherapeutic, targeted and immunosuppressive drugs in the treatment of cancer.